The future of upper extremity rehabilitation robotics: research and practice. Issue 6 (15th May 2020) - Vu, Philip P.; Chestek, Cynthia A.; Nason, Samuel R.; Kung, Theodore A.; Kemp, Stephen W.P.; Cederna, Paul S.
Abstract: The loss of upper limb motor function can have a devastating effect on people's lives. To restore upper limb control and functionality, researchers and clinicians have developed interfaces to interact directly with the human body's motor system. In this invited review, we aim to provide details on the peripheral nerve interfaces and brain‐machine interfaces that have been developed in the past 30 years for upper extremity control, and we highlight the challenges that still remain to transition the technology into the clinical market. The findings show that peripheral nerve interfaces and brain‐machine interfaces have many similar characteristics that enable them to be concurrently developed. Decoding neural information from both interfaces may lead to novel physiological models that may one day fully restore upper limb motor function for a growing patient population.